UMPSA distributes 3,000 bubur lambuk and gulai kawah to Kuantanese - Siti Nur Azwin, Zulkapri (UMPSA, 2025)
KUANTAN, 12 March 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) distributed bubur lambuk and gulai kawah for free to the Kuantanese through a communal work initiative involving student and staff volunteers from the Student Affairs and Alumni Department (JHEPA), UMPSA Advanced Education, Maxis Berhad, and Masjid Sultan Ahmad 1, recently.